A checklist of the oribatid mite species (Acari: Oribatida) of Brazil - Oliveira, Anibal R.; Argolo, Poliane S.; Moraes, Gilberto J. De; Norton, Roy A.; Schatz, Heinrich (Zootaxa, 2017)
A checklist of the oribatid mite species reported in Brazil is presented, including all published records up to 2015. A total of 576 described species in 206 genera and 83 families is presented. Information includes the names by which each species was reported in the Brazilian literature, its general known distribution and by Brazilian States, references, and remarks, when needed. As with most countries, there was a slow early accumulation of knowledge but in recent decades the pace of description has been relatively high. A graphical overview of the number of described oribatid mite species from Brazil in different decades is given. The proportion contributed by each of the major oribatid groups is generally similar to that of the overall world fauna, with a composition that reflects the South American fauna and all of the Neotropics in general. There is a relatively low percentage of primitive mites (Palaeosomata, Enarthronota) other than Lohmanniidae and Mesoplophoridae, which are quite diverse. The Brachypylina comprises about 68% of the oribatid mite fauna. In the checklist, 41% of the species are known only from Brazil, 37% from the Neotropical region, 13.5% have a wider distribution in the global tropical and subtropical regions, and 8.5% are considered cosmopolitan or semicosmopolitan species. The number of descriptions of new species since 2000 from Brazil (73 spp.) and South America (230) is high, but the oribatid mite fauna of these countries remains poorly known. Only continued studies can determine if the high number of species known only from Brazil is an indication of high endemism.